1982
DOI: 10.1007/bf00988313
|View full text |Cite
|
Sign up to set email alerts
|

Taste preferences of the common vampire bat (Desmodus rotundus)

Abstract: Taste preference tests, with simultaneous presentation of treated and untreated food, were administered to 24 common vampire bats (Desmodus rotundus). The bats received brief exposures to four different stimuli representing sweet, salty, sour, and bitter tastes, each at four different concentrations. Despite a strong location bias, the bats significantly (P < 0.01) avoided the highest concentrations of the salty, sour, and bitter tastes. Consumption of the sweet stimulus at all concentrations was similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
16
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 14 publications
10
16
1
1
Order By: Relevance
“…Behavioural tests have demonstrated that vampire bats possess poorly developed taste ability because they showed indifference to sweet and detected bitter, sour and salty tastants in high concentrations [11], and they even lost taste-aversion learning for poison avoidance [33]. Our genetic data are fully consistent with the behavioural tests.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Behavioural tests have demonstrated that vampire bats possess poorly developed taste ability because they showed indifference to sweet and detected bitter, sour and salty tastants in high concentrations [11], and they even lost taste-aversion learning for poison avoidance [33]. Our genetic data are fully consistent with the behavioural tests.…”
Section: Discussionsupporting
confidence: 81%
“…Second, many pseudogenized T2Rs in vampire bats suggest that their bitter taste is greatly reduced and the reduction of bitter taste was also observed behaviourally in Desmodus rotundus [11]. Third, the evolutionary conservation of several T2Rs and taste signaling pathway strongly support the behavioural finding in which vampire bats still retain some bitter taste ability, evidenced by the detection of bitter tastants in relatively higher concentrations [11]. Consistent with the genetic data supporting the view of retaining some bitter taste in vampire bats, anatomical studies discovered normal taste buds in the canonical taste structures [35] and electrophysiological recordings identified functional taste receptors in these bats [36].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Tas1r2 also is known to be pseudogenized in chicken, tongueless Western clawed frogs, and vampire bats (11,15). The loss of the sweet taste receptor in chicken and vampire bats is consistent with their sweet insensitive behavior (16,17). It is yet to be established how Western clawed frogs respond to sweeteners.…”
mentioning
confidence: 99%